The American novel in the 21st century: cultural contexts - literary developments - critical analyses - Basseler, Michael; Nünning, Ansgar; Völker, Nico (WVT-Handbücher zum literaturwissenschaftlichen Studium, 2019)
Focusing on the ways in which contemporary fiction and new genres of the novel are entangled with a variety of societal challenges and concerns, the aim of this volume is to provide students, university teachers, and literary scholars with a compact overview of the US-American novel in the first two decades of the new millennium. What are the dominant themes and recurring topics of recent American novels? How can the cultural dynamics of literary change in contemporary fiction be conceptualized, and what are the institutional, political, economic, cultural, ecological, and social contexts that have driven generic change in the American novel in the last fifteen to twenty years? What authors – established and new – have shaped the course of the novel in the 21st century? What are the most influential novels of the new millennium thus far, and how have they responded to, altered, and complicated our very notion of ‘the American novel’? The chapters in this handbook aim to address these questions in a manner that is at once systematic, clearly structured, and deliberately pluralistic and open, particularly with regard to the theoretical and methodological frameworks applied.
Keywords: Aufsatzsammlung; Geschichte 2001-2016; Roman; USA; Geschichte 2000-2019